2004
DOI: 10.1161/01.str.0000147041.00840.59
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Antihypertensive Regimens Based on Fosinopril or Hydrochlorothiazide With or Without Lipid Lowering by Pravastatin on Progression of Asymptomatic Carotid Atherosclerosis

Abstract: on behalf of PHYLLIS InvestigatorsBackground and Purpose-The Plaque Hypertension Lipid-Lowering Italian Study (PHYLLIS) tested whether (1) the angiotensin-converting enzyme (ACE) inhibitor fosinopril (20 mg per day) was more effective on carotid atherosclerosis progression than the diuretic hydrochlorothiazide (25 mg per day), (2) pravastatin (40 mg per day) was more effective than placebo when added to either hydrochlorothiazide or fosinopril, and (3) there were additive effects of ACE inhibitor and lipid-low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
24

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 24 publications
3
75
0
24
Order By: Relevance
“…Length of hospital stay, persistence on statin therapy and quality-of-life measures were not reported in any of the studies. ALLHAT-LLT 40 Bruckert et al 33 Muldoon et al 29 PHYLLIS 30 PREVEND-IT 31 Rejnmark et al 32 HYRIM 28 MEGA 24 ASCOT-LLA 36 Holmberg et al 26 Bone et al 23 Adverse events Twenty-one trials (n = 47 589) reported the number of participants who had serious adverse events. The trial-level relative risk could not be estimated for four trials that reported no events in either group.…”
Section: Other Outcomesmentioning
confidence: 99%
“…Length of hospital stay, persistence on statin therapy and quality-of-life measures were not reported in any of the studies. ALLHAT-LLT 40 Bruckert et al 33 Muldoon et al 29 PHYLLIS 30 PREVEND-IT 31 Rejnmark et al 32 HYRIM 28 MEGA 24 ASCOT-LLA 36 Holmberg et al 26 Bone et al 23 Adverse events Twenty-one trials (n = 47 589) reported the number of participants who had serious adverse events. The trial-level relative risk could not be estimated for four trials that reported no events in either group.…”
Section: Other Outcomesmentioning
confidence: 99%
“…In eight CIMT trials, the results showed a similar direction for both CIMT and event outcome measurements, while in seven CIMT trials, congruency with event trials depended on the choice of the primary outcome measure. In four trials 10, 12, 22,30) , expected effects were found for the mean maximum CIMT but not for the common CIMT for mean, whereas in three trials 8, 13, 15) an effect was found for the common CIMT and not for the mean maximum CIMT. Thus, when relying on the mean maximum CIMT only, three trials would have been falsely negative (no effect on CIMT, clear clinical events effect).…”
Section: Congruency Between Results For Mean Common and Mean Maximum mentioning
confidence: 75%
“…Through a reference check one additional trial was identified 32) . Ultimately, this resulted in 15 CIMT trials for analyses 5, 7-10, 12, 13, 15, 16, 18,19,21,22,30,32) . For each drug used in the CIMT trials, the corresponding event trials were searched, resulting in 15 clinical event trials for lovastatin, pravastatin, fluvastatin, simvastatin, atorvastatin, torcetrapib, rosuvastatin and ezetimibe, as presented in Table 2 [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…3 Similar results have been obtained in other trials such as the Hypertension Optimal Treatment (HOT), 4 the International Nifedipine GITS study Intervention as a Goal in Hypertension Treatment (INSIGHT) 5 and the Plaque Hypertension Lipid-Lowering Italian Study (PHYLLIS). 6 Blood pressure control and cardiovascular outcome…”
Section: Clinic Versus Ambulatory Blood Pressure Controlmentioning
confidence: 99%